Digitalisasi UMKM melalui Pemetaan Lokasi di Google Maps: Upaya Peningkatan Aksesibilitas Pasar dalam Program KKN di Desa Timbang Lawan, Dusun VIII - Fanny Himla Rizqya Pasaribu; Siti Hansyah Dewi Zai; Putri Zahra; Alfarizki Jaelani; Ilka Zulfria; Nurbaiti Nurbaiti (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2024)
The Community Service Program (KKN) in Timbang Lawan Village, Hamlet VIII, focused on the digitalization of Micro, Small, and Medium Enterprises (MSMEs) by emphasizing business location mapping through the Google Maps platform. This program was motivated by the low market visibility and accessibility experienced by village MSMEs, primarily due to limitations in utilizing digital technology as a means of promotion and marketing. Through a series of intensive mentoring, the KKN team conducted outreach, training on the use of digital devices, and technical guidance in the process of creating and managing business location points on Google Maps. The implementation of this program not only helped MSMEs obtain easily accessible digital identities but also expanded their marketing reach by increasing the ease of consumers in finding business locations. Based on monitoring results, a significant increase in the level of digital visibility of several MSMEs was seen, as well as an increase in the number of consumer visits to registered business locations. In addition, MSMEs demonstrated increased understanding and independence in utilizing digital technology for their business development. This digitalization program through location mapping is expected to be the first step in encouraging sustainable digital transformation of village MSMEs, strengthening local competitiveness, and supporting more inclusive community economic growth.